Three-dimensional porous super-hydrophobic composite coating as well as preparation method and application thereof

The three-dimensional porous superhydrophobic composite coating is prepared by spraying polydimethylsiloxane, stereosilicon, and hydrophobic silica, which solves the problems of complex preparation and environmental pollution in the prior art, and achieves simplicity and high efficiency Superhydrophobic coating with excellent drag reduction and corrosion resistance.

CN119161804APending Publication Date: 2024-12-20NORTHWESTERN POLYTECHNICAL UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411502277.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The preparation steps of existing three-dimensional porous superhydrophobic materials are complex, and fluorine-containing materials cause damage to the environment. The two-dimensional thin superhydrophobic surface is easily damaged in practical applications, resulting in failure of superhydrophobic properties and corrosion problems.

Method used

A three-dimensional porous superhydrophobic composite coating is prepared by spraying method using polydimethylsiloxane, stereosilicon oxide and hydrophobic silica, and a dense structure is formed by semi-curing treatment, avoiding the use of complex processes and fluorine-containing materials.

Benefits of technology

It realizes simple preparation of superhydrophobic coatings, has excellent drag reduction and long-term corrosion resistance, is suitable for various base materials, and does not contain fluorine substances, and has good environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161804A_ABST
    Figure CN119161804A_ABST
Patent Text Reader

Abstract

The invention discloses a three-dimensional porous super-hydrophobic composite coating as well as a preparation method and application thereof, and belongs to the technical field of preparation of anticorrosive coatings. The method for preparing the three-dimensional porous super-hydrophobic composite coating comprises the following steps: uniformly mixing first polydimethylsiloxane, a first curing agent and a first organic solvent to prepare a primer; coating the primer on a substrate material, and carrying out semi-curing treatment to obtain a bonding layer on the surface of the substrate; uniformly mixing second polydimethylsiloxane, a second curing agent, three-dimensional zinc oxide, hydrophobic silicon dioxide and a second organic solvent to prepare finish paint; and the surface of the bonding layer is coated with finish paint, curing treatment is conducted, and the three-dimensional porous super-hydrophobic composite coating is obtained on the surface of the substrate. The method is easy and convenient to operate, and damage of fluorine-containing materials to the environment is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of anti-corrosion coating preparation, and in particular relates to a three-dimensional porous super-hydrophobic composite coating and a preparation method and application thereof. Background Art

[0002] Superhydrophobicity is a special type of wettability, which generally refers to the spherical shape of water droplets on the solid surface, namely the Cassie-Baxter state, with a contact angle greater than 150 degrees and a rolling angle less than 10 degrees. Generally speaking, the lower the surface energy of the material, the better the hydrophobicity, and when the low surface energy material has a microscopic rough structure, an air film will form between the water droplets and the material, hindering the wetting of the material surface by water.

[0003] The construction of super-hydrophobic surfaces requires the satisfaction of two conditions: low surface free energy and appropriate surface microstructure. At present, there are several methods for preparing super-hydrophobic surfaces: the template method mainly replicates the rough structure on the template surface with low surface energy to obtain super-hydrophobicity. The laser etching method uses laser ablation to change the surface roughness to form a super-hydrophobic surface. The deposition method is to add a coating on the surface of the substrate through the particle deposition technology to make the substrate have super-hydrophobic properties. Most of the above methods construct super-hydrophobic surface structures, and this two-dimensional surface structure faces huge challenges in practical applications. For example, in the application of torpedoes, ships and other navigation fields, the destruction of the Cassie-Baxter state formed by the two-dimensional thin super-hydrophobic surface will lead to the failure of super-hydrophobic performance, further leading to the loss of drag reduction performance, and the occurrence of metal corrosion after seawater contacts the substrate. For this situation, researchers have proposed that although the Cassie-Baxter state is formed on the surface of the material, this does not mean that only the super-hydrophobicity of the two-dimensional surface is required, and the roughness in the bulk phase of the super-hydrophobic material is equally important.

[0004] The advantage of three-dimensional porous superhydrophobic coatings over two-dimensional surface coatings is that the loss of trapped air is relatively fast on a two-dimensional thin surface with a metastable superhydrophobic state, and the surface is completely wetted after the coating fails. In contrast, the three-dimensional structure keeps the air on the surface and throughout the bulk material. When water penetrates into the material, new water-air-material interfaces (i.e., superhydrophobic states) are continuously generated from the surface to the bulk, so the water penetration rate will slow down. Such a scenario will provide superhydrophobic coatings for drag reduction and long-term corrosion protection applications.

[0005] The traditional method of constructing three-dimensional porous superhydrophobic materials is to use a hard three-dimensional framework composite with low surface energy materials. The hard framework provides mechanical properties, such as anodized aluminum, stainless steel, diatomaceous earth, etc., and the low surface energy material provides superhydrophobic properties, such as fluorine-containing materials. However, the preparation steps of this type of three-dimensional porous structure are relatively complicated and difficult to prepare, and the use of fluorine-containing materials will cause damage to the environment. Summary of the invention

[0006] In view of the above problems, the present invention provides a three-dimensional porous super-hydrophobic composite coating and a preparation method and application thereof. The present invention is easy to operate and avoids the damage of fluorine-containing materials to the environment.

[0007] The first object of the present invention is to provide a method for preparing a three-dimensional porous super-hydrophobic composite coating, comprising the following steps:

[0008] The first polydimethylsiloxane, the first curing agent and the first organic solvent are mixed evenly to prepare a primer;

[0009] The primer is applied on the base material and semi-cured to obtain a bonding layer on the base surface;

[0010] The second polydimethylsiloxane, the second curing agent, the three-dimensional zinc oxide, the hydrophobic silica and the second organic solvent are uniformly mixed to prepare a topcoat;

[0011] A topcoat is coated on the surface of the bonding layer and cured to obtain a three-dimensional porous super-hydrophobic composite coating on the surface of the substrate.

[0012] In a preferred embodiment of the present invention, the curing temperature of the semi-curing treatment is 20°C to 120°C, and the curing time is 5min to 120min. For example, the curing temperature of the semi-curing treatment is 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, etc., and the curing time is 5min, 10min, 30min, 50min, 70min, 90min, 110min, 120min, etc., but it is not limited to the listed values, and other values ​​not listed in the above numerical range are also applicable.

[0013] In a preferred embodiment of the present invention, the mass ratio of the second polydimethylsiloxane, the three-dimensional zinc oxide and the hydrophobic silica is 1:1:0.5-1.5. For example, the mass ratio of the second polydimethylsiloxane, the three-dimensional zinc oxide and the hydrophobic silica is 1:1:0.5, 1:1:0.75, 1:1:1, 1:1:1.25, 1:1:1.5, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0014] In a preferred embodiment of the present invention, the mass ratio of the second polydimethylsiloxane, the three-dimensional zinc oxide and the hydrophobic silicon dioxide is 1:1:1.

[0015] In a preferred embodiment of the present invention, the curing temperature of the curing treatment is 20°C to 120°C, and the curing time is 1h to 24h. For example, the curing temperature of the curing treatment is 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, etc., and the curing time is 1h, 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0016] In a preferred embodiment of the present invention, the mass ratio of the first polydimethylsiloxane to the first curing agent is 10:2-3; for example, the mass ratio of the first polydimethylsiloxane to the first curing agent is 10:2, 10:2.2, 10:2.4, 10:2.6, 10:2.8, 10:3, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0017] The ratio of the first polydimethylsiloxane to the first organic solvent is 3 g to 4 g:9 mL. For example, the ratio of the first polydimethylsiloxane to the first organic solvent is 3 g:9 mL, 3.2 g:9 mL, 3.4 g:9 mL, 3.6 g:9 mL, 3.8 g:9 mL, 4 g:9 mL, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0018] In a preferred embodiment of the present invention, the mass ratio of the second polydimethylsiloxane to the second curing agent is 10:2-3; for example, the mass ratio of the second polydimethylsiloxane to the second curing agent is 10:2, 10:2.2, 10:2.4, 10:2.6, 10:2.8, 10:3, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0019] The ratio of the second polydimethylsiloxane to the second organic solvent is 2g to 3g:30mL. For example, the ratio of the second polydimethylsiloxane to the second organic solvent is 2g:30mL, 2.2g:30mL, 2.4g:30mL, 2.6g:30mL, 2.8g:30mL, 3g:30mL, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0020] In a preferred embodiment of the present invention, the first organic solvent is ethyl acetate and / or n-hexane.

[0021] The first organic solvent and the second organic solvent are the same.

[0022] The second object of the present invention is to provide a three-dimensional porous super-hydrophobic composite coating prepared by the above preparation method.

[0023] The third object of the present invention is to provide the application of the above three-dimensional porous super-hydrophobic composite coating in the preparation of anti-corrosion materials.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) Different from the previous template method, deposition method, laser etching method, and hard frame composite low surface energy material method, the present invention only needs to be sprayed and cured to prepare a super hydrophobic coating with excellent drag reduction performance and long-term corrosion resistance. It is not necessary to use a complicated preparation process to prepare a super hydrophobic coating, and the process flow is simple, and the damage of fluorine-containing materials to the environment is avoided. Different from the polydimethylsiloxane coating after curing as a primer binder in the traditional process, the present invention has carried out a semi-curing treatment to the polydimethylsiloxane primer coating, so that its surface produces an active group hydroxyl group, which can react with the silicon oxygen bond in the hydrophobic silica in the topcoat to generate a Si-O-Si covalent bond, and the Si-O-Si covalent bond generated by the reaction makes the super hydrophobic coating have a more compact structure. Therefore, it also has good mechanical stability and excellent corrosion resistance. The three-dimensional zinc oxide in the coating provides a three-dimensional structure with roughness and a certain low surface energy. The nano-scale hydrophobic nano-silica can partially fill the uneven holes formed by the three-dimensional zinc oxide. The use of two low surface energy materials, three-dimensional zinc oxide and hydrophobic silica, makes the surface energy of the coating lower, making the super-hydrophobic coating more excellent and stable under long-term use. The synergistic effect of the low surface energy materials, three-dimensional zinc oxide and gas-phase hydrophobic silica, makes the energy state of the coating surface lower and stable, so the coating has excellent super-hydrophobicity, drag reduction performance and long-term anti-corrosion performance.

[0026] (2) The present invention is universally applicable to most substrates, whether they are metal substrates or non-metal substrates; a resin with excellent bonding properties is selected as the bonding layer of the coating through semi-curing treatment, thereby ensuring the bonding strength between the coating and various substrates.

[0027] (3) The coating used in the present invention does not contain fluorine substances and will not cause harm to the environment.

[0028] (4) The dense three-dimensional porous structure super-hydrophobic coating of the present invention has high drag reduction performance and long-term anti-corrosion performance, which can meet the practical application of the super-hydrophobic coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Graphs showing contact angles and sliding angles of super-hydrophobic coatings with different coating ratios in Examples 1 to 5 of the present invention.

[0030] Figure 2 are the contact angles of different materials, wherein a is the contact angle of the aluminum plate in Example 1, b is the contact angle of the super-hydrophobic coating sprayed on the aluminum plate in Comparative Example 1; c is the contact angle of the super-hydrophobic coating sprayed on the aluminum plate in Comparative Example 2; d is the contact angle of the super-hydrophobic coating sprayed on the aluminum plate in Example 1.

[0031] Figure 3 Actual pictures of mechanical property tests of super-hydrophobic coatings prepared in Comparative Example 4 (a), Example 1 (b), and Comparative Example 5 (c).

[0032] Figure 4 is the infrared spectrum of the coating. Wherein, a is the infrared spectrum of the polydimethylsiloxane in the semi-cured state in Comparative Example 3; b is the infrared spectrum of the super hydrophobic coating in Example 1.

[0033] Figure 5 Surface scanning electron microscope image (a) and energy spectrum diagram of carbon (b), oxygen (c), silicon (d) and zinc (e) elements of the super-hydrophobic coating in Example 1.

[0034] Figure 6 (a) is a cross-sectional scanning electron microscope image of the super-hydrophobic coating in Example 1 and an energy spectrum diagram of carbon (b), oxygen (c), aluminum (d), silicon (e) and zinc (f) elements.

[0035] Figure 7 : Drag reduction performance test graph. a is the drag reduction performance test result graph of the super hydrophobic coating, the blank sample aluminum plate and the polydimethylsiloxane coating in Example 1, b is the drag reduction performance test result graph of the super hydrophobic coating, the blank sample aluminum plate and the polydimethylsiloxane coating in Comparative Example 3, and c is the drag reduction performance test result graph of the super hydrophobic coating and the blank sample stainless steel plate in Comparative Example 2.

[0036] Figure 8 The anticorrosion performance test result diagram of the super-hydrophobic coating in Example 1, Comparative Example 1 and Comparative Example 2. Wherein a is the Bode plot of the electrochemical impedance spectrum of the super-hydrophobic coating of Comparative Example 1; b is the Bode plot of the electrochemical impedance spectrum of the super-hydrophobic coating of Example 1; c is the Bode plot of the electrochemical impedance spectrum of the super-hydrophobic coating of Comparative Example 2.

[0037] Fig. 9 This is a sandpaper wear experiment of the super-hydrophobic coating in Example 1 of the present invention. DETAILED DESCRIPTION

[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] The present invention provides a method for preparing a three-dimensional porous super-hydrophobic composite coating, comprising the following steps:

[0040] The first polydimethylsiloxane, the first curing agent and the first organic solvent are mixed evenly to prepare a primer.

[0041] The primer is applied on the base material and semi-cured to obtain a bonding layer on the base surface;

[0042] The second polydimethylsiloxane, the second curing agent, the three-dimensional zinc oxide, the hydrophobic silicon dioxide and the second organic solvent are uniformly mixed to prepare a topcoat.

[0043] A topcoat is coated on the surface of the bonding layer and cured to obtain a three-dimensional porous super-hydrophobic composite coating on the surface of the substrate.

[0044] The underwater drag reduction mechanism of the three-dimensional porous super-hydrophobic composite coating prepared by the present invention is as follows: the polydimethylsiloxane, three-dimensional zinc oxide and hydrophobic nano-silica in the three-dimensional porous super-hydrophobic composite coating form a super-hydrophobic coating with low surface energy and reasonable surface roughness. When this super-hydrophobic coating with a three-dimensional porous structure is used underwater, it can form an air film on the surface to isolate the contact between the solid material and water, forming a Cassie-Baxter wetting state, so that the contact of the fluid on the coating surface is transformed from solid-liquid contact to gas-liquid contact, thereby reducing the surface friction and achieving the effect of drag reduction. During the long-term application of the coating, the structure and air film on the surface of the superhydrophobic coating may be destroyed due to the intrusion of external forces or severe disturbances in the flow field. If the material only has a two-dimensional superhydrophobic structure on the surface, it may cause the coating to fail and lose its drag reduction performance. The three-dimensional porous superhydrophobic composite coating can use the pore structure in the bulk phase to continuously form an air film to prevent the intrusion of liquid, and continuously form a liquid-air-solid contact interface structure (i.e., a superhydrophobic state), thereby ensuring the long-term usability of the coating.

[0045] The underwater anticorrosion mechanism of the three-dimensional porous super-hydrophobic composite coating prepared by the present invention is as follows: the impedance value of the three-dimensional porous super-hydrophobic composite coating remains at a high level after long-term immersion, and the impedance value is 10 9 Ω·cm 2This is because the pores in the coating capture air and store it in the coating. The presence of the air layer forms a Cassie-Baxter wetting state, which greatly reduces the actual contact area between the corrosive medium solution and the coating. In addition, the super-hydrophobic coating with a three-dimensional porous structure can use the pore structure in the bulk phase to continuously form an air film to prevent the intrusion of liquid. Even if it is immersed in a corrosive solution for a long time, the corrosive ions will not easily contact the coating substrate, and the corrosive ions Cl - The process of penetration into the coating is effectively inhibited, thereby reducing the occurrence of coating corrosion.

[0046] The substrate used in the present invention is one of aluminum alloy plate, stainless steel plate, steel plate, copper plate, nickel alloy plate, tin alloy plate, tantalum alloy plate, magnesium alloy plate, titanium alloy plate, wooden board, glass plate, polymethyl methacrylate plate, polyethylene terephthalate film, polyimide film, polyethylene film, polyvinyl chloride film, polypropylene film, polystyrene film woven fabric, printing paper, cultural paper, household paper, technical paper, knitted fabric and non-woven fabric.

[0047] It should be noted that the Al plate used in the present invention has a thickness of 2mm and 1mm, and is made of 7075 aluminum alloy, which is provided by Shenzhen Bomei Metal Materials Co., Ltd. 316 stainless steel plate is provided by Xinghua Zhongzhiyuan Stainless Steel Products Co., Ltd. Polydimethylsiloxane prepolymer and curing agent are purchased from Dow Corning, model Sylgard 184, that is, Sylgard 184 contains polydimethylsiloxane prepolymer and supporting curing agent. The three-dimensional zinc oxide used in the present invention is a four-needle zinc oxide, which is purchased from Angxing New Carbon Material Changzhou Co., Ltd., with a particle size of 10μm to 40μm. The hydrophobic silica used in the present invention is a gas-phase hydrophobic nano-silica purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., with a particle size of 7nm to 40nm. Ethyl acetate (EA, purity 99.5%), anhydrous ethanol (purity 99.5%) and NaCl (purity 99.5%) were purchased from Sinopharm Chemical Reagent Co., Ltd. Sandpaper was provided by 3M China Co., Ltd.

[0048] Example 1

[0049] Step 1: Grind a 10 cm × 10 cm × 0.1 cm base aluminum plate with 80 mesh, 220 mesh, and 400 mesh sandpaper in turn, perform ultrasonic cleaning after grinding, and clean the surface with anhydrous ethanol.

[0050] Step 2: 3.00 g of polydimethylsiloxane (PDMS) was dissolved in 9 mL of ethyl acetate, and then a curing agent was added according to a mass ratio of PDMS to curing agent of 10:2, and the mixture was stirred for 1 hour to obtain a uniformly mixed primer.

[0051] 2.00 g of PDMS was dissolved in 30 mL of ethyl acetate, and a curing agent was added according to a mass ratio of polydimethylsiloxane to curing agent of 10:2. 2.00 g of tetrapod-shaped zinc oxide powder was added thereto, and then 2.00 g of gas-phase hydrophobic nano-silica powder was added thereto. After stirring for 1 hour, a uniformly mixed milky white solution was obtained, i.e., the topcoat.

[0052] Step 3: Spray 20 mL of primer onto a 10 cm × 10 cm × 0.1 cm aluminum plate substrate, and then cure at 80°C for 10 min to obtain a semi-cured adhesive layer, such as Figure 6 As shown in a, the spray thickness of the primer is 115.87 μm.

[0053] Step 4: On the basis of the bonding layer obtained in step 3, 20 mL of topcoat is sprayed and cured at 80°C for 1 h to obtain a super hydrophobic coating. Figure 6 As shown in b, the spray thickness of the topcoat is 87.51 μm.

[0054] Example 2

[0055] Step 1: Grind a 10 cm × 10 cm × 0.1 cm base aluminum plate with 80 mesh, 220 mesh, and 400 mesh sandpaper in turn, perform ultrasonic cleaning after grinding, and clean the surface with anhydrous ethanol.

[0056] Step 2: 3.00 g of polydimethylsiloxane (PDMS) was dissolved in 9 mL of ethyl acetate, and then a curing agent was added according to a mass ratio of polydimethylsiloxane to curing agent of 10:2, and the mixture was stirred for 1 h to obtain a uniformly mixed primer.

[0057] 2.00 g of PDMS was dissolved in 30 mL of ethyl acetate, and a curing agent was added according to a mass ratio of polydimethylsiloxane to curing agent of 10:2. 2.00 g of tetrapod-shaped zinc oxide powder was added thereto, and then 1.00 g of fumed hydrophobic nano-silica powder was added thereto. After stirring for 1 hour, a uniformly mixed milky white solution was obtained, i.e., the topcoat.

[0058] Step 3: Spray 20 mL of the primer onto an aluminum plate substrate of 10 cm×10 cm×0.1 cm, and then cure it at 80° C. for 10 min to obtain a bonding layer in a semi-cured state.

[0059] Step 4: On the basis of the bonding layer obtained in step 3, 20 mL of topcoat is sprayed and cured at 80° C. for 1 h to obtain a super-hydrophobic coating.

[0060] Example 3

[0061] Step 1: Grind a 10 cm × 10 cm × 0.1 cm base aluminum plate with 80 mesh, 220 mesh, and 400 mesh sandpaper in turn, perform ultrasonic cleaning after grinding, and clean the surface with anhydrous ethanol.

[0062] Step 2: Dissolve 3.00 g of polydimethylsiloxane (PDMS) in 9 mL of ethyl acetate, then add the curing agent at a mass ratio of 10:2, and stir for 1 hour to obtain a uniformly mixed primer.

[0063] 2.00 g of PDMS was dissolved in 30 mL of ethyl acetate, and a curing agent was added according to a mass ratio of polydimethylsiloxane to curing agent of 10:2. 2.00 g of tetrapod-shaped zinc oxide powder was added thereto, and then 1.50 g of gas-phase hydrophobic nano-silica powder was added thereto. After stirring for 1 hour, a uniformly mixed milky white solution was obtained, i.e., the topcoat.

[0064] Step 3: Spray 20 mL of the primer onto an aluminum plate substrate of 10 cm×10 cm×0.1 cm, and then cure it at 80° C. for 10 min to obtain a bonding layer in a semi-cured state.

[0065] Step 4: On the basis of the bonding layer obtained in step 3, 20 mL of topcoat is sprayed and cured at 80° C. for 1 h to obtain a super-hydrophobic coating.

[0066] Example 4

[0067] Step 1: Grind a 10 cm × 10 cm × 0.1 cm base aluminum plate with 80 mesh, 220 mesh, and 400 mesh sandpaper in turn, perform ultrasonic cleaning after grinding, and clean the surface with anhydrous ethanol.

[0068] Step 2: Dissolve 3.00 g of polydimethylsiloxane (PDMS) in 9 mL of ethyl acetate, then add the curing agent at a mass ratio of 10:2, and stir for 1 hour to obtain a uniformly mixed primer.

[0069] 2.00 g of PDMS was dissolved in 30 mL of ethyl acetate, and a curing agent was added according to a mass ratio of polydimethylsiloxane to curing agent of 10:2. 2.00 g of tetrapod-shaped zinc oxide powder was added thereto, and then 2.50 g of gas-phase hydrophobic nano-silica powder was added thereto. After stirring for 1 hour, a uniformly mixed milky white solution was obtained, i.e., the topcoat.

[0070] Step 3: Spray 20 mL of the primer onto an aluminum plate substrate of 10 cm×10 cm×0.1 cm, and then cure it at 80° C. for 10 min to obtain a bonding layer in a semi-cured state.

[0071] Step 4: On the basis of the bonding layer obtained in step 3, 20 mL of topcoat is sprayed and cured at 80° C. for 1 h to obtain a super-hydrophobic coating.

[0072] Example 5

[0073] Step 1: Grind a 10 cm × 10 cm × 0.1 cm base aluminum plate with 80 mesh, 220 mesh, and 400 mesh sandpaper in turn, perform ultrasonic cleaning after grinding, and clean the surface with anhydrous ethanol.

[0074] Step 2: Dissolve 3.00 g of polydimethylsiloxane (PDMS) in 9 mL of ethyl acetate, then add the curing agent at a mass ratio of 10:2, and stir for 1 hour to obtain a uniformly mixed primer.

[0075] 2.00 g of PDMS was dissolved in 30 mL of ethyl acetate, and a curing agent was added according to a mass ratio of polydimethylsiloxane to curing agent of 10:2. 2.00 g of tetrapod-shaped zinc oxide powder was added thereto, and then 3.00 g of gas-phase hydrophobic nano-silica powder was added thereto. After stirring for 1 hour, a uniformly mixed milky white solution was obtained, i.e., the topcoat.

[0076] Step 3: Spray 20 mL of the primer onto an aluminum plate substrate of 10 cm×10 cm×0.1 cm, and then cure it at 80° C. for 10 min to obtain a bonding layer in a semi-cured state.

[0077] Step 4: On the basis of the bonding layer obtained in step 3, 20 mL of topcoat is sprayed and cured at 80° C. for 1 h to obtain a super-hydrophobic coating.

[0078] Example 6

[0079] Step 1: Grind a 10 cm × 10 cm × 0.2 cm base aluminum plate with 80 mesh, 220 mesh, and 400 mesh sandpaper in turn, perform ultrasonic cleaning after grinding, and clean the surface with anhydrous ethanol.

[0080] Step 2: Dissolve 4.00 g of polydimethylsiloxane (PDMS) in 9 mL of n-hexane, then add the curing agent at a mass ratio of 10:3, and stir for 1 hour to obtain a uniformly mixed primer.

[0081] 3.00 g of PDMS was dissolved in 30 mL of n-hexane, and a curing agent was added according to a mass ratio of polydimethylsiloxane to curing agent of 10:3. 2.00 g of tetrapod-shaped zinc oxide powder was added thereto, and then 3.00 g of fumed hydrophobic nano-silica powder was added thereto. After stirring for 1 hour, a uniformly mixed milky white solution was obtained, i.e., the topcoat.

[0082] Step 3: Spray 20 mL of the primer onto an aluminum plate substrate of 10 cm×10 cm×0.1 cm, and then cure it at 120° C. for 5 min to obtain a bonding layer in a semi-cured state.

[0083] Step 4: On the basis of the bonding layer obtained in step 3, 20 mL of topcoat is sprayed and cured at 120° C. for 3 h to obtain a super-hydrophobic coating.

[0084] Example 7

[0085] Step 1: Grind a 10 cm × 10 cm × 0.2 cm base aluminum plate with 80 mesh, 220 mesh, and 400 mesh sandpaper in turn, perform ultrasonic cleaning after grinding, and clean the surface with anhydrous ethanol.

[0086] Step 2: Dissolve 3.50 g of polydimethylsiloxane (PDMS) in 4.5 mL of ethyl acetate and 4.5 mL of n-hexane, then add the curing agent at a mass ratio of 10:2.5, and stir for 1 h to obtain a uniformly mixed primer.

[0087] 2.50 g of PDMS was dissolved in 15 mL of ethyl acetate and 15 mL of n-hexane, and a curing agent was added according to a mass ratio of polydimethylsiloxane to curing agent of 10:2.5. 2.00 g of tetrapod-shaped zinc oxide powder was added thereto, and then 3.00 g of gas-phase hydrophobic nano-silica powder was added thereto. After stirring for 1 hour, a uniformly mixed milky white solution was obtained, i.e., the topcoat.

[0088] Step 3: Spray 20 mL of the primer onto an aluminum plate substrate of 10 cm×10 cm×0.1 cm, and then cure it at 20° C. for 120 min to obtain a bonding layer in a semi-cured state.

[0089] Step 4: On the basis of the bonding layer obtained in step 3, 20 mL of topcoat is sprayed and cured at 20° C. for 24 h to obtain a super-hydrophobic coating.

[0090] Comparative Example 1

[0091] Step 1: Grind a 10 cm × 10 cm × 0.1 cm base aluminum plate with 80-mesh, 220-mesh and 400-mesh sandpapers in turn, perform ultrasonic cleaning after grinding, and clean the surface with anhydrous ethanol.

[0092] Step 2: Dissolve 3.00 g of polydimethylsiloxane (PDMS) in 9 mL of ethyl acetate, then add the curing agent at a mass ratio of 10:2, and stir for 1 hour to obtain a uniformly mixed primer.

[0093] 2.00 g of PDMS was dissolved in 30 mL of ethyl acetate, and a curing agent was added according to a mass ratio of polydimethylsiloxane to curing agent of 10:2. 2.00 g of tetrapod-shaped zinc oxide powder was added thereto, and after stirring for 1 h, a uniformly mixed milky white solution was obtained, namely, the topcoat.

[0094] Step 3: Spray 20 mL of the primer onto an aluminum plate substrate of 10 cm×10 cm×0.1 cm, and then cure at 80° C. for 10 min to obtain a bonding layer.

[0095] Step 4: On the basis of the bonding layer obtained in step 3, 20 mL of topcoat was sprayed and cured at 80° C. for 1 h to obtain a super hydrophobic coating, which was recorded as T-ZnOw Coating.

[0096] Comparative Example 2

[0097] Step 1: Grind a 10 cm × 10 cm × 0.1 cm base aluminum plate with 80 mesh, 220 mesh, and 400 mesh sandpaper in turn, perform ultrasonic cleaning after grinding, and clean the surface with anhydrous ethanol.

[0098] Step 2: Dissolve 3.00 g of polydimethylsiloxane (PDMS) in 9 mL of ethyl acetate, then add the curing agent at a mass ratio of 10:2, and stir for 1 hour to obtain a uniformly mixed primer.

[0099] 2.00 g of PDMS was dissolved in 30 mL of ethyl acetate, and a curing agent was added according to a mass ratio of polydimethylsiloxane to curing agent of 10:2. 2.00 g of gas-phase hydrophobic nano-silica powder was added thereto, and after stirring for 1 hour, a uniformly mixed milky white solution was obtained, i.e., the topcoat.

[0100] Step 3: Spray 20 mL of the primer onto an aluminum plate substrate of 10 cm×10 cm×0.1 cm, and then cure at 80° C. for 10 min to obtain a bonding layer.

[0101] Step 4: On the basis of the bonding layer obtained in step 3, 20 mL of topcoat is sprayed and cured at 80° C. for 1 h to obtain a super hydrophobic coating, which is recorded as SiO2 Coating.

[0102] Comparative Example 3

[0103] Step 1: Grind a 10 cm × 10 cm × 0.1 cm base aluminum plate with 80 mesh, 220 mesh, and 400 mesh sandpaper in turn, perform ultrasonic cleaning after grinding, and clean the surface with anhydrous ethanol.

[0104] Step 2: Dissolve 3.00 g of polydimethylsiloxane (PDMS) in 9 mL of ethyl acetate, then add the curing agent at a mass ratio of 10:2, and stir for 1 hour to obtain a uniformly mixed primer.

[0105] Step 3: Spray 20 mL of the primer onto an aluminum plate substrate of 10 cm×10 cm×0.1 cm, and then cure at 80° C. for 1 h to obtain a polydimethylsiloxane coating, which is referred to as PDMS.

[0106] Comparative Example 4

[0107] Step 1: Grind a 10 cm × 10 cm × 0.1 cm base aluminum plate with 80 mesh, 220 mesh, and 400 mesh sandpaper in turn, perform ultrasonic cleaning after grinding, and clean the surface with anhydrous ethanol.

[0108] Step 2: Dissolve 3.00 g of polydimethylsiloxane (PDMS) in 9 mL of ethyl acetate, then add the curing agent at a mass ratio of 10:2, and stir for 1 hour to obtain a uniformly mixed primer.

[0109] 2.00 g of PDMS was dissolved in 30 mL of ethyl acetate, and a curing agent was added according to a mass ratio of polydimethylsiloxane to curing agent of 10:2. 2.00 g of tetrapod-shaped zinc oxide powder was added thereto, and then 2.00 g of gas-phase hydrophobic nano-silica powder was added thereto. After stirring for 1 hour, a uniformly mixed milky white solution was obtained, i.e., the topcoat.

[0110] Step 3: Spray 20 mL of primer on an aluminum plate substrate of 10 cm×10 cm×0.1 cm without curing treatment, directly spray 20 mL of topcoat, and then cure at 80° C. for 1 h to obtain a super-hydrophobic coating.

[0111] Comparative Example 5

[0112] Step 1: Grind a 10 cm × 10 cm × 0.1 cm base aluminum plate with 80 mesh, 220 mesh, and 400 mesh sandpaper in turn, perform ultrasonic cleaning after grinding, and clean the surface with anhydrous ethanol.

[0113] Step 2: Dissolve 3.00 g of polydimethylsiloxane (PDMS) in 9 mL of ethyl acetate, then add the curing agent at a mass ratio of 10:2, and stir for 1 hour to obtain a uniformly mixed primer.

[0114] 2.00 g of PDMS was dissolved in 30 mL of ethyl acetate, and a curing agent was added according to a mass ratio of polydimethylsiloxane to curing agent of 10:2. 2.00 g of tetrapod-shaped zinc oxide powder was added thereto, and then 2.00 g of gas-phase hydrophobic nano-silica powder was added thereto. After stirring for 1 hour, a uniformly mixed milky white solution was obtained, i.e., the topcoat.

[0115] Step 3: Spray 20 mL of the primer onto an aluminum plate substrate of 10 cm×10 cm×0.1 cm, and then cure at 80° C. for 30 min to obtain a bonding layer in a fully cured state.

[0116] Step 4: On the basis of the bonding layer obtained in step 3, 20 mL of topcoat is sprayed and cured at 80° C. for 1 h to obtain a super-hydrophobic coating.

[0117] In order to verify the performance of the super-hydrophobic coating prepared in the present invention, the coatings prepared in Examples 1 to 5 and Comparative Examples 1 to 5 were tested, and the test results are specifically shown as follows.

[0118] like Figure 1 As shown, in Example 1 to Example 5, the coating mass ratio of the super-hydrophobic coating of Example 1 is that the mass ratio of polydimethylsiloxane, four needle-shaped zinc oxide and gas-phase hydrophobic nano-silica is 1: 1: 1, and the super-hydrophobic coating of the ratio has the highest contact angle and the lowest sliding angle, indicating that 1: 1: 1 is the optimal ratio of super-hydrophobic coating. And too high or too low ratio will affect the contact angle performance of coating. This is because the two low surface energy materials of four needle-shaped zinc oxide and gas-phase hydrophobic nano-silica in topcoat are responsible for providing super-hydrophobic performance, and polydimethylsiloxane provides appropriate mechanical properties as a binder, so theoretically the ratio of four needle-shaped zinc oxide and gas-phase hydrophobic nano-silica is larger, the super-hydrophobic performance of material surface is stronger, and the water contact angle of material is larger. However, due to the characteristics of low surface energy materials, the energy state of their surface is relatively stable, and foreign substances are not easy to adhere to their surface. Therefore, a ratio of tetrapod zinc oxide and vapor-phase hydrophobic nano-silica greater than 1:1:1 will cause the coating to fall off, destroy the micro-rough structure of the surface, cause performance deterioration, and the water contact angle of the material will become lower.

[0119] like Figure 2 As shown in a, the base aluminum plate is hydrophilic, and the contact angle of water on the aluminum plate is 63°, which shows that the pure aluminum plate is easily adhered to by water droplets. After the super-hydrophobic coating is sprayed on the surface of the aluminum plate, a rough structure is formed on its surface, and there are substances with low surface energy. These two factors provide the coating with super-hydrophobicity, such as Figure 2 As shown in b, the contact angle of water on the super-hydrophobic coating of Comparative Example 1 is 150°; Figure 2 As shown in c, the contact angle of water on the super-hydrophobic coating of Comparative Example 2 is 156°; Figure 2 As shown in d, the contact angle of water on the super-hydrophobic coating of Example 1 is 161°, and the water droplets on the three super-hydrophobic coatings are all spherical, that is, super-hydrophobic. We take the super-hydrophobic coating in Example 1 with the best performance for subsequent testing.

[0120] Figure 3 a, b and c in are respectively the physical pictures of the super-hydrophobic coating prepared after the primer is sprayed with topcoat in the uncured (Comparative Example 4), semi-cured (Example 1), and fully cured (Comparative Example 5) states for mechanical property testing. If the super-hydrophobic structure is not destroyed enough after the coating is worn, the remaining coating can still support the water droplets to form the Casey state, i.e., the super-hydrophobic state. If the surface of the super-hydrophobic coating is not uniform enough, even if it is not damaged, the water droplets will also produce the phenomenon of pinning due to the ups and downs of the microscopic rough structure. The test of the rolling angle can more intuitively characterize the uniformity of the coating. After the sandpaper wear experiment after finger wiping and on 1500 mesh sandpaper, 50g load wear 4000cm, Figure 3 Figures a and c show that part of the coatings in Comparative Examples 4 and 5 are damaged, resulting in the exposure of the metal substrate, water droplets adhere to the coating surface, and the superhydrophobic property is lost. Figure 3 b in the figure shows that after the finger wiping and sandpaper abrasion tests of Example 1, the coating surface is not damaged, indicating that the semi-cured primer has excellent adhesion and well ensures the bonding between the metal substrate and the coating. Water droplets roll down quickly on the inclined coating surface and do not adhere to the coating surface, proving that the coating still has excellent superhydrophobic properties after the test, and further proving that the coating prepared according to the preparation method of the present invention has better performance.

[0121] like Figure 4 a in the figure is the infrared spectrum of the polydimethylsiloxane coating prepared in comparative example 3 in a semi-cured state. It can be seen that 3601 cm -1 The characteristic peak of hydroxyl group appeared at , indicating that after a specific time of semi-curing treatment, active hydroxyl groups appeared on its surface, providing active sites for subsequent reaction with gas-phase nano-hydrophobic silica; Figure 4 b is the infrared spectrum of the super-hydrophobic coating in Example 1, and it can be seen that 2960 cm -1 The characteristic absorption peak at 451cm belongs to the stretching vibration of C–H. -1 The characteristic absorption peak at 1410cm corresponds to the asymmetric and symmetric stretching and bending vibrations of Si–O–Si bonds. -1 The peak at 1253 cm-1 can be attributed to the Zn–O bond vibration. -1 The peak at 1051cm corresponds to the symmetric deformation absorption peak in Si–CH3. -1 and 1035cm -1The band at 790cm is associated with the asymmetric Si–O–Si stretching vibration. -1 The peak at corresponds to the Si–C stretching in Si–CH 3. The test results of infrared spectrum show the successful preparation of super hydrophobic coating.

[0122] Figure 5 In a is the scanning electron microscope image of the super-hydrophobic coating surface in Example 1, it can be seen that the coating surface has obvious roughness and has a porous structure, this is because the zinc oxide used in the present invention has a special four-pin structure, and its structure can form a three-dimensional porous structure by reasonable stacking. Spraying method is adopted in the present invention, with four pin-shaped zinc oxide as a three-dimensional framework, polydimethylsiloxane as an adhesive, and nano silicon dioxide fills holes on the one hand to make the hole structure more uniform, and on the other hand as the addition of low surface energy material makes hydrophobicity stronger. The present invention uses these three materials by the mode of spraying, stacked layer by layer, and each layer, that is, between the coatings in the two-dimensional direction, the four pin-shaped structure load silicon dioxide of zinc oxide crosses each other to form a two-dimensional porous structure. Between different two-dimensional layers, the two-dimensional porous layer of lower floor provides support for the two-dimensional porous layer of upper floor, so as to form a three-dimensional porous structure stacked layer by layer.

[0123] Figure 5 In the figure, b, c, d and e are the energy spectra of four elements, namely carbon, oxygen, silicon and zinc. It can be seen that the elements on the coating surface are distributed more evenly.

[0124] Figure 6 a in the figure is a scanning electron microscope image of the cross section of the super-hydrophobic coating in Example 1. It can be seen that the coating not only has an obviously rough and porous structure on the surface, but also has a three-dimensional porous structure in the bulk phase. Figure 6 Figures b, c, d, e and f are energy spectra of five elements, namely carbon, oxygen, aluminum, silicon and zinc, respectively. It can be seen that the elements in the coating present obvious stratification, which further proves the success of the spraying process of the present invention.

[0125] A rheometer (HAAKE MARS III, Germany) was used to test the drag reduction performance of the coating. The rheometer test mode is the plate-plate mode, and the constructed flow field is the Couette flow field. The upper plate is the P35 titanium alloy plate rotor that comes with the rheometer, with a diameter of 18.0±0.0035mm. The lower plate is the test sample, and the gap between the upper and lower plates is 1mm. The test fluid is water, and the volume of liquid added to the 1mm gap each time is 0.96mL. During the test, in order to ensure that the temperature of the working fluid remains constant to avoid fluctuations in its viscosity that affect the test results, the rheometer temperature control system is used to set the working temperature to 25±0.5℃. The coating was subjected to a drag reduction test, and the following results were obtained: Figure 7 The graph showing the variation of coating surface shear force with Reynolds number is shown in Figure 1. Figure 7a, b and c in the figure are the test result diagrams of Example 1, Comparative Example 1 and Comparative Example 2 respectively. It should be noted that: Figure 7 The suffix W in the middle refers to the measurement medium of water when the drag reduction performance test is performed. Wherein a is the drag reduction performance test result diagram of the super-hydrophobic coating, the blank sample aluminum plate (Al sheet) and the polydimethylsiloxane coating in Example 3 in Example 1; b is the drag reduction performance test result diagram of the polydimethylsiloxane coating in the super-hydrophobic coating, the blank sample aluminum plate and the comparative example 3 in the comparative example 1; c is the drag reduction performance test result diagram of the super-hydrophobic coating and the blank sample stainless steel plate (316sheet) in the comparative example 2. It can be seen that the blank control group has the maximum friction force at the same Reynolds number, indicating that the fluid flows through the surface of the aluminum plate due to its hydrophilicity. Adsorption, resulting in increased friction, super-hydrophobic coating has the minimum friction force at the same Reynolds number, indicating that the super-hydrophobic surface forms an air film due to the super-hydrophobic state, so that the fluid flows through the coating surface. When the solid-liquid contact is transformed into gas-liquid contact, the friction resistance is reduced.

[0126] Table 1 Drag reduction test results

[0127] coating Drag reduction rate (%) Example 1 17.264 Comparative Example 1 9.714 Comparative Example 2 10.252

[0128] The drag reduction rate test was calculated with a blank sample as the control group, and the drag reduction rate test results are shown in Table 1. It can be seen that the super-hydrophobic coating in Example 1 has the highest drag reduction rate. This is because the synergistic effect of the two low surface energy substances in the coating makes the energy state of the coating surface more stable, and compared with the single low surface energy substance in Comparative Examples 1 and 2, the surface is less likely to adhere to foreign substances such as water droplets.

[0129] Table 2 Test results of specific surface area

[0130] coating Porosity (%) Total pore volume (mL / g) <![CDATA[Total pore area (m 2 / g)]]> Example 1 28.0930 0.1915 1.832 Comparative Example 1 37.5463 0.2815 4.368 Comparative Example 2 35.4254 0.2854 2.864

[0131] And from the data in Table 2, it can be seen that the super-hydrophobic coating in Example 1 has a more dense and uniform three-dimensional porous structure, which can reduce the phenomenon of water droplets pinning and adhering on its surface due to the uneven pore structure, thereby causing increased resistance.

[0132] The super hydrophobic coatings obtained in Example 1, Comparative Example 1 and Comparative Example 2, and the polydimethylsiloxane coating in Comparative Example 3 were subjected to long-term anti-corrosion tests. In the anti-corrosion test, in order to simulate the service of the three-dimensional porous super hydrophobic coating in seawater, the coating was subjected to electrochemical impedance spectroscopy test using a three-electrode system, wherein the working electrode was a different sample, the reference electrode was a silver chloride electrode, the auxiliary electrode was a platinum electrode (10mm×10mm×0.1mm), and the test platform was an electrochemical workstation (CHI660E, China). The coating was sprayed on a 316 stainless steel disc with a diameter of 15mm. The sample was immersed in a 3.5wt.% NaCl solution at room temperature, and the effective area of ​​the sample surface was controlled to 1cm 2 After the open circuit voltage (OCP) stabilizes, that is, the voltage fluctuation is less than 10mV, the experiment begins. -2 ~10 5 The electrochemical impedance spectroscopy test results are shown in the figure below: Figure 8 shown. Figure 8 a, b and c in the figure are the Bode diagrams of super hydrophobic coatings. Figure 8 0D, 6D, 14D and 31D refer to the number of days that the samples were immersed in 3.5wt.% NaCl solution as 0 day, 6 days, 14 days and 31 days.

[0133] The results show that Example 1, Figure 8 The impedance value of the super hydrophobic coating in b after immersion for 31 days at 0.01 Hz is about 10 9 Ω·cm 2 ;like Figure 8 As shown in a and c, the impedance values ​​of the coatings in Comparative Example 1 and Comparative Example 2 at 0.01 Hz after immersion for 31 days are both about 10 8 Ω·cm 2 The impedance value of the coating in comparative example 3 is only 10 5 Ω·cm 2 . In summary, after immersion for 31 days, the impedance value of Example 1 at 0.01Hz is 4 orders of magnitude greater than that of the polydimethylsiloxane coating in Comparative Example 3, and 1 order of magnitude greater than that of the other super-hydrophobic coatings. The above results show that the super-hydrophobic coating with a three-dimensional porous structure in Example 1 has a denser three-dimensional pore structure, which reduces the probability of corrosion ions contacting the substrate through micropores, so the super-hydrophobic coating of Example 1 has the most excellent long-term anti-corrosion performance.

[0134] Fig. 9The sandpaper is a sandpaper wear test sandpaper of the superhydrophobic coating in Example 1 of the present invention. On 1500 mesh sandpaper, the contact angle and rolling angle test graphs after different wear cycles under a load of 50g, and one cycle is 40cm; after 4000cm of wear, the coating still has a contact angle greater than 150° and a low sliding angle less than 1°, indicating that the coating has excellent mechanical properties.

[0135] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0136] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a three-dimensional porous super-hydrophobic composite coating, characterized in that: The following steps are involved: The first polydimethylsiloxane, the first curing agent and the first organic solvent are mixed evenly to prepare a primer; The primer is applied on the base material and semi-cured to obtain a bonding layer on the base surface; The second polydimethylsiloxane, the second curing agent, the three-dimensional zinc oxide, the hydrophobic silica and the second organic solvent are uniformly mixed to prepare a topcoat; A topcoat is coated on the surface of the bonding layer and cured to obtain a three-dimensional porous super-hydrophobic composite coating on the surface of the substrate.

2. The method for preparing a three-dimensional porous super-hydrophobic composite coating according to claim 1, characterized in that: The curing temperature of the semi-curing treatment is 20°C to 120°C, and the curing time is 5min to 120min.

3. The method for preparing a three-dimensional porous super-hydrophobic composite coating according to claim 1, characterized in that: The mass ratio of the second polydimethylsiloxane, the three-dimensional zinc oxide and the hydrophobic silicon dioxide is 1:1:0.5-1.

5.

4. The method for preparing a three-dimensional porous super-hydrophobic composite coating according to claim 3, characterized in that: The mass ratio of the second polydimethylsiloxane, the three-dimensional zinc oxide and the hydrophobic silicon dioxide is 1:1:

1.

5. The method for preparing a three-dimensional porous super-hydrophobic composite coating according to claim 1, characterized in that: The curing temperature of the curing treatment is 20°C to 120°C, and the curing time is 1h to 24h.

6. The method for preparing a three-dimensional porous super-hydrophobic composite coating according to claim 1, characterized in that: The mass ratio of the first polydimethylsiloxane to the first curing agent is 10:2-3; the ratio of the first polydimethylsiloxane to the first organic solvent is 3g-4g:9mL.

7. The method for preparing a three-dimensional porous super-hydrophobic composite coating according to claim 1, characterized in that: The mass ratio of the second polydimethylsiloxane to the second curing agent is 10:2-3; The ratio of the second polydimethylsiloxane to the second organic solvent is 2 g to 3 g:30 mL.

8. The method for preparing a three-dimensional porous super-hydrophobic composite coating according to claim 1, characterized in that: The first organic solvent is ethyl acetate and / or n-hexane; The first organic solvent and the second organic solvent are the same.

9. A three-dimensional porous super-hydrophobic composite coating prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the three-dimensional porous super-hydrophobic composite coating according to claim 9 in the preparation of anti-corrosion materials.

Citation Information

Patent Citations

  • Highly-wear-resistant super-hydrophobic composite coating and preparation method thereof

    CN105419450A

  • Hydrophobic anticorrosive coating and preparation method thereof

    CN111534195A

  • SiO2-coated ZnO super-hydrophobic coating material with micro-nano coarse structure, and preparation method, application and use method of SiO2-coated ZnO super-hydrophobic coating material

    CN113354964A

  • Preparation method of super-hydrophobic hot liquid composite coating

    CN114773946A

  • Hydrophobic coating as well as preparation method and application thereof

    CN115260899A